2020
DOI: 10.3390/antibiotics9070382
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Methicillin-Resistant Staphylococcus aureus (MRSA) among Medical Students in Tertiary Institution in Central Malaysia

Abstract: Methicillin-resistant Staphylococcus aureus or MRSA infection is virulent and presents with a broad spectrum of severity. Limited regional reports that specifically outlined the potential risk of medical students being part of the dissemination of MRSA in healthcare settings were noted. This study aims to assess the prevalence and contributory factors of colonization of MRSA on neckties, headscarves, and ID badges among medical students in a local medical university in Malaysia. A cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Research conducted among healthy individuals in Malaysia revealed a low prevalence rate of S. aureus from nasal swabs of medical students (9.24%) and dental students (18.0%) [60,61]. A higher prevalence of S. aureus was observed from oral cavity samples (40.0%) and hand swab samples of food handlers (95.0%) from Ampang Jaya and Klang Valley respectively [45,62].…”
Section: Colonisationmentioning
confidence: 99%
“…Research conducted among healthy individuals in Malaysia revealed a low prevalence rate of S. aureus from nasal swabs of medical students (9.24%) and dental students (18.0%) [60,61]. A higher prevalence of S. aureus was observed from oral cavity samples (40.0%) and hand swab samples of food handlers (95.0%) from Ampang Jaya and Klang Valley respectively [45,62].…”
Section: Colonisationmentioning
confidence: 99%
“…Thus, that is a significant cause of mortality and morbidity in immunosuppressed patients, patients on hemodialysis, with prolonged hospitalizations and advanced age, besides smoking, alcoholism and chronic respiratory diseases (Ma et al, 2011;Rampal et al, 2020). In 2017, the microorganism was included in the World Health Organization's (WHO) List of Priority Pathogens, ratifying its relevance on the world stage (Szymanek-Majchrzak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%